The inverse of an equation is the opposite of the equation
The inverse of the function is [tex]y =2 \pm \sqrt{28 + 4x[/tex]
How to determine the inverse of the function
The equation is given as:
[tex]2(x - 2)^2 = 8(7 + y)[/tex]
Divide both sides of the equation by 2
[tex](x - 2)^2 = 4(7 + y)[/tex]
Open the bracket
[tex](x - 2)^2 = 28 + 4y[/tex]
Take the square roots of both sides
[tex]x - 2 = \pm\sqrt{28 + 4y[/tex]
Add 2 to both sides
[tex]x =2 \pm \sqrt{28 + 4y[/tex]
Swap the occurrences of x and y
[tex]y =2 \pm \sqrt{28 + 4x[/tex]
Hence, the inverse of the function is [tex]y =2 \pm \sqrt{28 + 4x[/tex]
Read more about inverse functions at:
https://brainly.com/question/8120556